2013
DOI: 10.1002/eat.22171
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic hunger and binge eating among women with eating disorders

Abstract: Results suggest that hedonic processes may be important in stimulating binge eating. Furthermore, hedonic appetite may facilitate weight restoration in AN. Further research should investigate whether pre-treatment PFS scores have prognostic significance with respect to eating disorder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 29 publications
3
54
0
3
Order By: Relevance
“…Finally, our patient samples included both restricting and binge-purging individuals. A recently published study (32) showed that binge-purging AN patients have a hedonic appetite higher than that of restricting anorexics. Therefore, differences in the modulation of reward-related processes between the 2 subtypes of AN patients may have affected our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, our patient samples included both restricting and binge-purging individuals. A recently published study (32) showed that binge-purging AN patients have a hedonic appetite higher than that of restricting anorexics. Therefore, differences in the modulation of reward-related processes between the 2 subtypes of AN patients may have affected our findings.…”
Section: Discussionmentioning
confidence: 98%
“…a dessert after dinner), but some experience more persistent preoccupation with palatable foods, defined as hedonic hunger (Finlayson, King, & Blundell, 2007;Lowe & Levine, 2005). The Power of Food Scale (PFS Lowe et al, 2009) measures this construct and is associated with frequency and intensity of food craving (Forman et al, 2007), as well as the development (Lowe et al, under review) and severity of binge eating in obese (Ochner, Green, van Steenburgh, Kounios, & Lowe, 2009) and eating disordered populations (Witt & Lowe, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…These types of foods are salient to BED. They are preferred and craved during binges, are more likely to be consumed for reasons other than hunger, their high palatability would render them more difficult to limit or to control, and their greater caloric value would contribute to the distress, shame, and guilt that is characteristic of BED and other binge-eating conditions (Boggiano, Turan, Maldonado, Oswald, & Shuman, 2013; Dalton, Blundell, & Finlayson, 2013; Davis et al, 2008, 2009; Drewnowski, 1998; Gendall, Sullivan, Joyce, Carter, & Bulik, 1997; Hill & Peters, 1998; Kales, 1990; Thomas, Doshi, Crosby, & Lowe, 2011; White & Grilo, 2005; Witt & Lowe, 2014; Yanovski, 2003). The PEMS differs from other eating-related cognitive and behavioral measures in that it probes why one eats palatable foods (i.e., eating as a means to meet a certain end) rather than assessing addictive-like behavior with food (Gearhardt, Corbin, & Brownell, 2009) or the extent to which various emotions and cues trigger food intake (Arnow, Kenardy, & Agras, 1995; van Strien, Frijters, Bergers, & Defares, 1986).…”
Section: Introductionmentioning
confidence: 99%